Effects of lotus seedpod oligomeric procyanidins on the inhibition of AGEs formation and sensory quality of tough biscuits - Chen, Ziting; Tan, Jiangying; Qin, Jiabin; Feng, Nianjie; Liu, Qianting; Zhang, Chan; Wu, Qian (Frontiers in Nutrition, 2022)
The advanced glycation end products (AGEs) are formed in baked products through the Maillard reaction (MR), which are thought to be a contributing factor to chronic diseases such as heart diseases and diabetes. Lotus seedpod oligomeric procyanidins (LSOPC) are natural antioxidants that have been added to tough biscuit to create functional foods that may lower the risk of chronic diseases. The effect of LSOPC on AGEs formation and the sensory quality of tough biscuit were examined in this study. With the addition of LSOPC, the AGEs scavenging rate and antioxidant capacity of LSOPC-added tough biscuits were dramatically improved. The chromatic aberration (ΔE) value of tough biscuits containing LSOPC increased significantly. Higher addition of LSOPC, on the other hand, could effectively substantially reduced the moisture content, water activity, and pH of LSOPC toughen biscuits. These findings imply that using LSOPC as additive not only lowers the generation of AGEs, but also improves sensory quality of tough biscuit.